Assessing dissolved organic matter in the Johannesburg-Sulfur autotrophic denitrification system using excitation—emission matrix fluorescence spectroscopy with a parallel factor analysis. Issue 50 (26th October 2016) - Li, Haibo; Zhou, Beihai; Tian, Zhiyong; Du, Erdeng; Tu, Xiang; Song, Yonghui; Wang, Siyu; Sun, Chen
Abstract: A novel system integrating Johannesburg (JHB) and sulfur autotrophic denitrification (SAD) process was proposed with the purpose of efficient removal of organic matter and nitrogen when treating low COD/TN ratio municipal wastewater. The characteristics and fate of dissolved organic matter in the Johannesburg-Sulfur autotrophic denitrification (JHB-SAD) system were investigated using excitation–emission matrix fluorescence spectroscopy with a parallel factor analysis. Three components were identified including tryptophan-like (component C 1 ), tyrosine-like (component C 2 ), and fulvic-like (component C 3 ) materials. The tyrosine-like and tryptophan-like materials, which were more abundant than fulvic-like materials, were the dominant components of the raw municipal wastewater in Shenyang North Wastewater Treatment Plant. In the JHB-SAD system, the tyrosine-like and tryptophan-like materials were more efficiently removed than the fulvic-like materials, and the removal efficiencies of the three components were 80.8% (tryptophan-like materials), 72.5% (tyrosine-like materials), and 33.4% (fulvic-like materials), respectively. Furthermore, the removal performance of the three components varied in the different zones of the JHB-SAD system. The tryptophan-like and fulvic-like materials were removed in the pre-anoxic, anaerobic, and aerobic zones. The tyrosine-like materials were mainly degraded in the anoxic and aerobic zones; then, they were released by the bacteria in the SAD reactor. In addition, the tryptophan-like materials had a very significant positive linear correlation with the concentrations of soluble chemical oxygen demand.